2003
DOI: 10.1002/acp.927
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic, semantic and phonetic influences in spoken warning signal words

Abstract: Three experiments are reported which explore the relationship between semantic, acoustic and phonetic variables in the judgement of eight warning signal words. Experiment 1 shows that listeners can distinguish very clearly between urgent and non-urgent versions of the words when spoken by real speakers, and that some signal words such as 'deadly' and 'danger' score more highly than words such as 'attention' and 'don't'. It also shows that the three dimensions of perceived urgency, appropriateness and believabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Additionally, it was found that an urgent utterance of the messages resulted in louder sounds, with higher pitch and pitch range. Edworthy et al [8] extended these findings, observing that signal words spoken urgently are perceived as more urgent, believable and appropriate as well. In our study, we use the above guidelines in the warnings, matching the urgency of the utterances to the urgency of the signified events.…”
Section: Designing Urgency In Speechmentioning
confidence: 67%
See 1 more Smart Citation
“…Additionally, it was found that an urgent utterance of the messages resulted in louder sounds, with higher pitch and pitch range. Edworthy et al [8] extended these findings, observing that signal words spoken urgently are perceived as more urgent, believable and appropriate as well. In our study, we use the above guidelines in the warnings, matching the urgency of the utterances to the urgency of the signified events.…”
Section: Designing Urgency In Speechmentioning
confidence: 67%
“…These results also further support the claim that participants valued more being warned about important events and can further justify why higher ratings of annoyance for L H messages were acceptable according to participants' comments, while for L L they were not. This also relates to [8], where highly urgent messages were perceived as more appropriate. As a guideline, warnings of high criticality can be more alerting even at the cost of more annoyance.…”
Section: Discussionmentioning
confidence: 99%
“…Baldwin [2] also observed lower reaction times to urgent words, presented with higher signal intensity. Edworthy et al [3] found that urgently spoken signal words were perceived as more urgent and appropriate.…”
Section: Multimodal Displays and Urgencymentioning
confidence: 99%
“…This may influence their relative urgency when spoken as compared to when in written form. Edworthy et al (2003b) found that when using synthesized voices, some words were rated has having lower levels of perceived urgency than research on text or natural speech presentations of the same words had suggested. These tended to be words that were difficult to voice with emphasis; 'lethal' and 'warning' in particular were rated lower than would be expected.…”
Section: Urgencymentioning
confidence: 89%